Active methodology and learning styles in the teaching process of the research methodology course of a faculty health sciences - Matzumura Kasano, Juan P. (2018)
Introduction. The educational model focused on learning attempts to provide the student a more important role in the process of acquiring knowledge, for this it is necessary to identify preferences or learning style of the students. Objectives. Analysis the influence of the use of active methodology and learning styles in students of the methodology course of undergraduate research. Methods. Quantitative study of quasi-experimental, prospective longitudinal design, the study population consisted of undergraduate students of the research methodology course. A non-probabilistic sample was used for convenience, consisting of 79 students. The instrument used was the learning style test developed by David Kolb. The implementation of the active methodology was carried out during the development of the course. Results The participation of the students during the development of classes and the use of texts presented a significant increase. The assimilator learning style corresponded 78,5% and 12,6% for the divergent before the implementation of the methodology and at the end of the study, the students modified their learning style in a significant way with a predominance of assimilator learning style 62 % and 22,8% for the convergent style. Conclusions. The active methodology allows the active participation of the student through questions, contributions and encourages the use of texts. It also significantly modifies the learning style towards an assimilator and convergent style.